2017
DOI: 10.1097/htr.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

P300 Event-Related Potentials Differentiate Better Performing Individuals With Traumatic Brain Injury: A Preliminary Study of Semantic Processing

Abstract: The recruitment of frontal areas after traumatic brain injury may represent compensatory neural mechanisms utilized to successfully maximize task performance. The P300 in a semantic processing paradigm may be a sensitive marker of neural plasticity that could be used to improve functional outcomes in cognitive remediation paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Advanced P300 activity was found at the frontal electrode of participants while working memory was being used, unlike younger individuals, in whom greater posterior activation was found. Another study of individuals with posttraumatic brain injury28 found that worse performance on neuropsychological tests was associated with decreased P300 amplitude relative to controls, although a typical P300 parietal wave response was evident. On the other hand, participants who performed better on the neuropsychological tests had robust amplitude for the P300, characterized by the recruitment of anterior brain regions, in addition to parietal activation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Advanced P300 activity was found at the frontal electrode of participants while working memory was being used, unlike younger individuals, in whom greater posterior activation was found. Another study of individuals with posttraumatic brain injury28 found that worse performance on neuropsychological tests was associated with decreased P300 amplitude relative to controls, although a typical P300 parietal wave response was evident. On the other hand, participants who performed better on the neuropsychological tests had robust amplitude for the P300, characterized by the recruitment of anterior brain regions, in addition to parietal activation.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers28 hold that P300 may be a sensitive marker of neural plasticity that could be used to improve functional results in paradigms of cognitive remediation. In view of the correlations reported here, we assume that stimulation of cognition in the practice setting, especially attention and working memory, may result in improved verbal fluency and language among elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Event-related potentials (P300) is an objective index to reflect the severity and the prognosis judgment of patients with cognitive impairment [ 17 , 18 ]. In the present study, we noted that, before treatment, there were no significant differences in the latency and amplitude of P300 among three groups ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…2 Low P300 amplitude for speech stimuli correlated with worse recovery prognosis in coma patients after severe brain injury. 15 Several studies showed a correlation of mismatch negativity (MMN) and P300 prominence with consciousness recovery in coma patients. 6…”
mentioning
confidence: 99%
“…2 Low P300 amplitude for speech stimuli correlated with worse recovery prognosis in coma patients after severe brain injury. 15 Several studies showed a correlation of mismatch negativity (MMN) and P300 prominence with consciousness recovery in coma patients. 6 A paradigm that includes event-related potential (ERP) registration has the advantage of complex stimuli processing visualization.…”
mentioning
confidence: 99%